Systemic lupus erythematosus associated with sickle-cell disease: a case report and literature review ... : الذئبة الحمامية الجهازية المرتبطة بمرض الخلايا المنجلية: تقرير حالة ومراجعة الأدبيات ... - M. Maamar; Z. Tazi-Mezalek; H. Harmouche; W. Mounfaloti; M. Adnaoui; M. Aouni (OpenAlex, 2012)
The occurrence of systemic lupus erythematosus has been only rarely reported in patients with sickle-cell disease. We describe the case of a 23-year-old North-African woman with sickle-cell disease and systemic lupus erythematosus, and discuss the pointers to the diagnosis of this combination of conditions and also present a review of literature. The diagnosis of systemic lupus erythematosus was delayed because our patient's symptoms were initially attributed to sickle-cell disease. Physicians should be alerted to the possible association of sickle-cell disease and systemic lupus erythematosus so as not to delay correct diagnosis and initiation of appropriate treatment. ... : نادراً ما تم الإبلاغ عن حدوث الذئبة الحمامية الجهازية في المرضى الذين يعانون من مرض الخلايا المنجلية. نصف حالة امرأة من شمال إفريقيا تبلغ من العمر 23 عامًا مصابة بمرض الخلايا المنجلية والذئبة الحمامية الجهازية، ونناقش مؤشرات تشخيص هذا المزيج من الحالات ونقدم أيضًا مراجعة للأدبيات. تأخر تشخيص الذئبة الحمامية الجهازية لأن أعراض مريضنا كانت تُعزى في البداية إلى مرض الخلايا المنجلية. يجب تنبيه الأطباء إلى الارتباط المحتمل لمرض الخلايا المنجلية والذئبة الحمامية الجهازية حتى لا يؤخر التشخيص الصحيح وبدء العلاج المناسب. ...